2016
DOI: 10.21273/hortsci.51.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity, Population Structure, and Formation of a Core Collection of 1197 Citrullus Accessions

Abstract: Watermelon belongs to the genus Citrullus. There have been continuing interests in breeding of watermelon for economic benefits, but information on the scope and utilization of genetic variations in Citrullus is still limited. The present study was conducted in 2012–13, to evaluate the genetic diversity and population structure of the 1197 line watermelon collection maintained by the Beijing Vegetable Research Center (BVRC), which belongs to seven <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 26 publications
0
34
1
Order By: Relevance
“…Both seed batches have now been removed from the National Plant Germplasm System (NPGS Web Site, http:// www.ars-grin.gov/cgi-bin/npgs/) and are no longer distributed. The so-called core collection of Zhang & al. (2016) also includes germplasms labeled as Citrullus (such as PI 671961, PI 618817, and CXG in their figure 3: all labeled C. naudinianus), but that are Cucumis myriocarpus (see footnotes in our Table 2).…”
Section: Species Relationships and Key Traits Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Both seed batches have now been removed from the National Plant Germplasm System (NPGS Web Site, http:// www.ars-grin.gov/cgi-bin/npgs/) and are no longer distributed. The so-called core collection of Zhang & al. (2016) also includes germplasms labeled as Citrullus (such as PI 671961, PI 618817, and CXG in their figure 3: all labeled C. naudinianus), but that are Cucumis myriocarpus (see footnotes in our Table 2).…”
Section: Species Relationships and Key Traits Inmentioning
confidence: 99%
“…Conclusions. -The need for an up-dated classification of Citrullus has often been stressed, most recently by Zhang & al. (2016), and the present assignment of 50 available names to seven biological species, along with morphological and ecological traits as well as a tabulation of chromosome counts should help towards that goal.…”
Section: Citrullus Ecirrhosusmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSR markers generated a total of 135 putative alleles (different fragment size) in both sampled populations (Table 3). This was higher than 133 alleles detected by Zhang et al (2016) who evaluated 23 SSR markers on 1197 watermelon core collections. Nimmakayala et al (2009) reported a total of 169 alleles amplified in watermelon cultivars.…”
Section: Discussionmentioning
confidence: 61%
“…2009; Solmaz et al, 2010;Zhang et al, 2016). Watermelon breeding programs in the country establish the genetic relationships of germplasm through phenotypic characterization.…”
mentioning
confidence: 99%